الرقابة القضائية على ممارسة صاحب العمل لسلطته التأديبية دراسة تحليلية مقارنة - جرادة, نضال جمال (Revue jurisprudence, 2019)
The employer's disciplinary authority is a natural consequence of his right to administer his project. There must be a penalty to ensure that the regulations, orders and work instructions of the employer are respected for the purpose of organizing the work in the project. Otherwise, these regulations and directives will remain ineffective in the light of the absence of the penalty for violating them. Despite the approval of the authority of punishment and rewarding to punish the guilty employee, such authority may be abused. So, it is found that labor laws set up rules to prevent the employer from abusing his disciplinary authority. When the worker is punished as a result of an error committed by him on the occasion of his performance of the work, this disciplinary penalty is subject to the supervision of the judiciary to examine the extent of the employer's compliance with the disciplinary controls prescribed in the laws and regulations. It is worth mentioning that the legislative shortage that the Palestinian labor law has in this context led me to study this topic, especially in the light of the high rates of labor disputes in different courts. We have reached a set of results in the legislative, judicial and executive fields to provide more comprehensive protection for the worker.